Pengaruh Faktor Eksternal Terhadap Preferensi Masyarakat dalam Memilih Produk Tabungan Mudharabah pada Bank Syariah di Kabupaten Sambas - Admaja, Surya; Kusnadi, Iwan (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to determine whether there is a positive and significant influence between culture, social, and marketing partially and simultaneously on community preferences in choosing Mudharabah savings products at Islamic Banks in Sambas Regency. This study uses a quantitative approach method of associative-causal nature. The population in this study is all Mudharabah savings customers at Islamic Banks in Sambas Regency, determining the sample size using Roscoe's theory resulted in a total sample of 40 respondents. The type of data used is primary data obtained from questionnaires. The ordinal data obtained were then converted into interval data. Furthermore, the data were processed with validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS 23.The results showed that partially, there was no positive and significant influence between culture on community preferences as seen from the value of t count < t table (0.369 < 2.02809) with a significance value of 0.714 > 0.05, there was no positive and significant influence between social on community preferences as seen from t count < t table (0.505 < 2.02809) with a significance value of 0.616 > 0.05, there was a positive and significant influence between marketing on community preferences as seen from the value of t count > t table (3.598 > 2.02809) with a significance value of 0.001 < 0.05. Simultaneously, there is a positive and significant influence between culture, social, and marketing on community preferences as seen from the value of F count > F table (8.533 > 2.87) with a significance value of 0.000 < 0.05. Furthermore, the Adjusted R Square value is 0.367, this means that the influence of culture, social, and marketing on community preferences is 36.7%, while the remaining 63.3% is influenced by other variables not included in this study.